Fashion films: trends and terms in fashion communication - Queiroz Campos, Amanda (2023)
The present research reckons fashion films as a current and widely valued modality in fashion communication. In addition to the audiovisual resources and the temporal reference, the possibility of creating narratives – fantastic, documental, and others – mainly serves to bring the consumer public closer, to go beyond the materiality of the product, making the relationship with products and brands more moving and exciting. The goal is to analyze different audiovisual narratives of fashion films released by international brands in 2021 and 2022, identifying communication trends in the field of fashion. To this end, we applied discourse analysis in combination with visual analysis to describe, analyze and interpret the messages conveyed in fashion films and subsequently identify trends and approaches in the branded content. The films were: (1) C’est L’Amour, Adidas and Gucci; (2) Olivia Wilde Directs Her Own Vogue Video, Vogue; (3) Victor da Justa, SPFWN53; (4) Storm chasing, Alexander McQueen; and (5) Sankofa – Mile Lab.